Can a Multi-Component Intervention Improve Pediatric Service Delivery in Guangzhou? - Hu, Fang; Guo, Shuaijun; Lu, Jianjun; Li, Ziang; Song, Yanyan; Pérez-Escamilla, Rafael; Lin, Suifang; Hu, Yifei (Frontiers in Public Health, 2021)
Background: Accessible, equitable and efficient pediatric service is critical to achieve optimal child health. This study aimed to evaluate the effectiveness of a multi-component intervention on the pediatric health system over two different periods in Guangzhou. Methods: Based on the World Health Organization (WHO) “six building blocks” model and Donabedian’s “Structure-Process-Outcomes” framework, an intervention package was developed to increase financial and human resouce investment to strengthen basic health care and strive for a better quality of pediatric care. This multi-component intervention package was conducted in Guangzhou to improve the pediatric service delivery during two stages (2011 to 2014 and 2016 to 2019). The main outcome indicators were the changes in the allocation of pediatricians and pediatric beds, pediatric service efficiency, and the impact of pediatricians on child mortality. Results: We found that pediatricians per 1000 children (PPTC) and pediatric beds per 1000 children (PBPTC) increased from 1.07 and 2.37 in 2010 to 1.37 and 2.39 in 2014, then to 1.47 and 2.93 in 2019, respectively. Infant mortality rate (IMR) and under-5 mortality rate (U5MR) dropped from 5.46‰ and 4.04‰ in 2010 to 4.35‰ and 3.30‰ in 2014 then to 3.26‰ and 2.37‰ in 2019. The Gini coefficients of PPTC and PBPTC decreased from 0.48 and 0.38 in 2010, to 0.35 and 0.28 in 2014, then to 0.35 and 0.22 in 2019, respectively, representing the improvement of pediatric resources distribution according to service population. However, equalities in the spatial distribution were not improved much. The average efficiency of pediatric service fluctuated from 2010 to 2019. A unit increase in PPTC was associated with an 11% reduction in IMR and a 16% reduction in U5MR. Conclusions: Findings suggest this multi-component intervention strategy is effective, particularly on the reduction of child mortality. In future, more rigorous and multi-faceted indicators should be integrated in a comprehensive evaluation of the intervention.